Exploring a BPMS system for learning production management with simulation of manufacturing scenarios - De Campos, Renato [UNESP]; De Souza Rodrigues, José [UNESP] (My University, 2021)
The approach by processes, and business processes management (BPM) in particular, has been increasingly studied by academia and more adopted in the business environment, due to its capabilities. Therefore, educational establishments should consider teaching and learning of technologies (such as BPMS systems) that systematize and facilitate the analysis, design and (re)engineering of organizations. Simulation systems can be used to develop active learning and improve student engagement in engineering classes. This work aims to explore the use of BPM in such a way that it might integrate with pedagogical practices. Specifically, we carry out a preliminary evaluation of a BPMS system in the simulation of manufacturing processes, aimed at the future teaching and learning of undergraduate students on Production Engineering courses, for the assimilation of knowledge about Production Management through life-like examples. The context under consideration was the manufacture of products assuming different physical layouts, which represent the positioning of the transforming resources of a hypothetical production environment, determining how raw material and transformed resources will flow through operational procedures. Using a version of the Bizagi software modeling and simulation, we identify the facility with which the processes are modeled, as well as quick data entry and simulation of these processes, could be modeled with the software analyzed. However, some difficulties in modeling and simulation with Bizagi were discovered with regards to the consideration of manufacturing processes by batch. That is, in this initial investigation of the simulation functionalities of the system, it was not possible to use batches of different sizes. This difficulty limits the use of the BPMS for simulating manufacturing scenario concepts and, consequently, the use of the system for pedagogical activities in production management classes.
Keywords: Active learning; Process management; Production management; Simulation